Procedures of city transport systems’ planning - Juškevičius, P. (Journal of Civil Engineering and Management, 1995)
The article starts with looking into a treatment of the objects of city transport systems planning: administrative (determined) and systematic approach, that are of importance for the principles of planning and its quality. The major shortages of the traditional planning are the following: its determination, narrow functional attitude towards the processes of transportation, lack of evaluation of the interrelations between a city structure and its transport system. There are several obstacles to shift to the planning of higher quality, namely poorly arranged information supply, shortage of mathematical models for transport processes and relevant soft ware. Considering the gained experience of transport system planning and professional knowledge on transport systems, a new methodology of planning is presented. A major stress here is put on the complex of transport system functioning, the consequences and the price. Article in Lithuanian. Miestų susisiekimo sistemų planavimo proceso procedūros First Published Online: 26 Jul 2012